A high coverage reference transcriptome assembly of pea (Pisum sativum L.) mycorrhizal roots - A. M. Afonin; I. V. Leppyanen; O. A. Kulaeva; O. Y. Shtark; I. A. Tikhonovich; E. A. Dolgikh; V. A. Zhukov (Вавиловский журнал генетики и селекции)
Arbuscular mycorrhiza (AM) is an ancient mutualistic symbiosis formed by 80–90 % of land plant species with the obligatorily biotrophic fungi that belong to the phylum Glomeromycota. This symbiosis is mutually beneficial, as AM fungi feed on plant photosynthesis products, in turn improving the efficiency of nutrient uptake from the environment. The garden pea (Pisum sativum L.), a widely cultivated crop and an important model for genetics, is capable of forming triple symbiotic systems consisting of the plant, AM fungi and nodule bacteria. As transcriptomic and proteomic approaches are being implemented for studying the mutualistic symbioses of pea, a need for a reference transcriptome of genes expressed under these specific conditions for increasing the resolution and the accuracy of other methods arose. Numerous transcriptome assemblies constructed for pea did not include mycorrhizal roots, hence the aim of the study to construct a reference transcriptome assembly of pea mycorrhizal roots. The combined transcriptome of mycorrhizal roots of Pisum sativum cv. Frisson inoculated with Rhizophagus irregularis BEG144 was investigated, and for both the organisms independent transcriptomes were assembled (coverage 177x for pea and 45x for fungus). Genes specific to mycorrhizal roots were found in the assembly, their expression patterns were examined with qPCR on two pea cultivars, Frisson and Finale. The gene expression depended on the inoculation stage and on the pea cultivar. The investigated genes may serve as markers for early stages of inoculation in genetically diverse pea cultivars.